Cuneiform Texts in The Otago Museum: A preliminary report - Horowitz, Wayne; Reeves, Scott; Stillman, Larry; Zilberg, Peter; White, Moira (Buried History: The Journal of the Australian Institute of Archaeology, 2016)
The Otago Museum, Dunedin, has a collection of over 150 cuneiform tablets.This paper describes the background of the collection and presents a brief analysis of two tablets from the collection, one historical and the other mathematical.